EFFECT OF HARVEST DATE AND STALK SECTION ON SELECTED STRENGTH CHARACTERISTICS OF TURKISH OREGANO (ORIGANUM ONITES L) - Yilmaz, Deniz; Jasinskas, Algirdas (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The time required to harvest plant crops is important to the plant properties. It is affected by design of the harvest equipment and the desire for high-quality products with low energy usage. Materials and Methods: Strength characteristics of Origanum onites L., an important medicinal aromatic plant, harvested on 2, 9, 16 and 23 July, 2012–2014 (H1, H2, H3 and H4, respectively) were measured at the bottom and top sections of the stalk. Measurements included maximum force, bio-yield force, shearing force, bending stress, shearing stress, shearing energy, and shearing deformation. Results: The highest maximum force (35.17 N) was at H4 on the bottom section, and the lowest was at H1 on the top. Maximum values for bio-yield force, shearing force, and bending stress were at H4 on the bottom section, and corresponding minimum values were at H1 on the top section. Shearing stress decreased at successive harvest dates for both stalk sections. The minimum shearing energy was at H4, (0.13 J and 0.06 J for bottom and top, respectively). Strength measurements for bottom sections of the stalk were greater than those for top sections. Conclusion: When reduced harvesting force is needed because of harvester design or harvest procedures, harvesting near the top of the stalk is recommended.